2016
DOI: 10.1083/jcb.201602074
|View full text |Cite
|
Sign up to set email alerts
|

A disulfide bond in the TIM23 complex is crucial for voltage gating and mitochondrial protein import

Abstract: Here, Ramesh et al. show that import and oxidation of Tim17, a membrane-embedded subunit of the mitochondrial protein import machinery, are mediated by the mitochondrial disulfide relay, although its disulfide bond is formed differently than soluble intermembrane space proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 58 publications
(105 reference statements)
2
44
1
Order By: Relevance
“…A recent report highlights that the Tim17 disulfide bond is critical for protein translocation and channel gating (79). Additionally, mutants lacking the Tim17 disulfide bond showed larger Tim21-bound TIM23 complexes and depleted TIM23 core complex, suggesting "extensive remodelling of TIM23-complex" (79). On the other hand, our findings highlight that the mutations in G/AXXXG/A motifs result in complete destabilization of the TIM23 complex due to defective recruitment of Pam18, Pam16, and Tim21.…”
Section: Tim17 Maintains Mtdna and Tim23 Complex Integritycontrasting
confidence: 48%
See 1 more Smart Citation
“…A recent report highlights that the Tim17 disulfide bond is critical for protein translocation and channel gating (79). Additionally, mutants lacking the Tim17 disulfide bond showed larger Tim21-bound TIM23 complexes and depleted TIM23 core complex, suggesting "extensive remodelling of TIM23-complex" (79). On the other hand, our findings highlight that the mutations in G/AXXXG/A motifs result in complete destabilization of the TIM23 complex due to defective recruitment of Pam18, Pam16, and Tim21.…”
Section: Tim17 Maintains Mtdna and Tim23 Complex Integritycontrasting
confidence: 48%
“…Presumably, the loss of membrane polarity due to mutation in G/AXXXG/A motifs can arise as a consequence of perturbed helix-helix packing between Tim23 and Tim17. A recent report highlights that the Tim17 disulfide bond is critical for protein translocation and channel gating (79). Additionally, mutants lacking the Tim17 disulfide bond showed larger Tim21-bound TIM23 complexes and depleted TIM23 core complex, suggesting "extensive remodelling of TIM23-complex" (79).…”
Section: Tim17 Maintains Mtdna and Tim23 Complex Integritymentioning
confidence: 99%
“…Therefore, interaction of the N-terminal domain of ScTim17 with the presequence is necessary for import of the precursor protein through the TIM23-17 channel. Recent data also showed that cysteine residue at position 10 is involved in disulfide bond formation with cysteine at position 77 [42,43]. Mutation of any of these two cysteines is detrimental for Tim17 function, particularly the gating of the TIM23 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Strains used to compare the effect of Djp1, Tom70 and Mim1 (ISY7475, djp1, tom70/71tom70/71djp1, mim1) were already described in (6). The tim17 ts mutant is described in (21).…”
Section: Yeast Strainsmentioning
confidence: 99%